The impact of temperature on mortality in argentinean municipalities - García Witulski, Christian Martín (2021)
Fil: García Witulski, Christian Martín. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina